DENITRIFICATION AND NITROUS OXIDE EMISSIONS FROM RIPARIAN FORESTS SOILS EXPOSED TO PROLONGED NITROGEN RUNOFF - Ullah S.; Zinati G.M. (My University, 2006)
Compared to upland forests, riparian forest soils have greater potential to remove nitrate (NO3) from agricultural runoff through denitrification. It is unclear, however, whether prolonged exposure of riparian soils to nitrogen (N) loading will affect the rate of denitrification and its end products. This research assesses the rate of denitrification and nitrous oxide (N2O) emissions from riparian forest soils exposed to prolonged nutrient runoff from plant nurseries and compares these to similar forest soils not exposed to nutrient runoff. Nursery runoff also contains high levels of phosphate (PO4). Since there are conflicting reports on the impact of PO4 on the activity of denitrifying microbes, the impact of PO4 on such activity was also investigated. Bulk and intact soil cores were collected from N-exposed and non-exposed forests to determine denitrification and N2O emission rates, whereas denitrification potential was determined using soil slurries. Compared to the non-amended treatment, denitrification rate increased 2.7- and 3.4-fold when soil cores collected from both N-exposed and non-exposed sites were amended with 30 and 60 µg NO3-N g−1 soil, respectively. Net N2O emissions were 1.5 and 1.7 times higher from the N-exposed sites compared to the non-exposed sites at 30 and 60 µg NO3-N g−1 soil amendment rates, respectively. Similarly, denitrification potential increased 17 times in response to addition of 15 µg NO3-N g−1 in soil slurries. The addition of PO4 (5 µg PO4-P g−1) to soil slurries and intact cores did not affect denitrification rates. These observations suggest that prolonged N loading did not affect the denitrification potential of the riparian forest soils; however, it did result in higher N2O emissions compared to emission rates from non-exposed forest soils.
Keywords: CHRONIC NITROGEN LOADING; DENITRIFICATION; NITROUS OXIDE EMISSIONS; NITROGEN SATURATION; NURSERY RUNOFF; RIPARIAN WETLANDS; PHOSPHORUS LOADING; WATER QUALITY